Chitosan oligosaccharide alleviates DON-induced liver injury via suppressing ferroptosis in mice - Mengjie Liu; Zhenlin Li; Jie Li; Guorong Yan; Chaoqi Liu; Qingqiang Yin; Yeqiang Liu; Xiaoxiang Xu (Ecotoxicology and Environmental Safety)
Chitosan oligosaccharide (COS), a water-soluble derivative of chitin, has been recognized for its diverse biological properties. Deoxynivalenol (DON) is a prevalent mycotoxin, causing extreme liver damage. However, the mechanism whereby COS alleviates DON-induced liver injury remains unclear. In the present study, C57BL/6 mice were randomly divided into four groups: control (CON), DON (1.0 mg/d/kg BW DON), COS (200 mg/d/kg BW COS), and COS+DON (200 mg/d/kg BW COS + 1.0 mg/d/kg BW DON), with a period of 28 days. The results indicated that COS effectively reversed DON-induced weight loss, elevated liver index, and liver hemorrhage and swelling in mice. Moreover, COS significantly reduced liver reactive oxygen species (ROS) levels, malondialdehyde (MDA) content, and lactate dehydrogenase (LDH) release in DON-exposed mice, while restoring the activity of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and total antioxidant capacity (T-AOC). Further investigations revealed that COS modulated the expressions of pro-inflammatory cytokines and anti-apoptotic proteins through stimulation of the Nrf2/HO-1 signaling pathway and suppression of the NF-κB signaling pathway. Additionally, COS inhibited ferroptosis by modulating the SLC7A11/GSH/GPX4 pathway and the expression of FTH1 and FLC proteins, thereby reducing lipid peroxidation accumulation and iron overload. In summary, this research showed that COS mitigated DON-induced liver injury in mice by alleviating DON-induced oxidative stress, inflammation, apoptosis, and ferroptosis via modulating the Nrf2/HO-1/NF-κB and GPX4 signaling pathways. These results offer a theoretical basis for the development and application of COS as a novel liver protectant and propose innovative therapeutic strategies for combating DON-induced liver damage.